2019
DOI: 10.33828/sei.v30.i3.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of using Digitally Supported Concept Maps Method in Science Classes in Primary Education on the Academic Success and Students’ Opinions

Abstract: Visual teaching materials have been reported to be efficient tools in the teaching-learning process (Abebe and Davidson, 2012;Bergeron et al., 1994;Yaşar and Şeremet, 2010). Visual teaching materials are often the illustrations of our oral knowledge, such as movies, computer and television screenshots, slides, photographs, and concept maps (Akgün, 2000). Visual teaching materials become assistants and guides for students in gathering attention, analyzing, and synthesizing information. A welldesigned schematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…This feature (digital vs physical/paper-and-pencil ones) is often categorised under the term 'type of response' (Hartmeyer et al, 2018). Brandstädter et al (2012) and Uygur (2019) have examined the efficacy of the digital type of response in relation to students' performance. In both studies, their statistical analysis between pre-and post-tests showed improved students' performance when using the digital concept maps in comparison with the paper-and-pencil ones.…”
Section: Introductionmentioning
confidence: 99%
“…This feature (digital vs physical/paper-and-pencil ones) is often categorised under the term 'type of response' (Hartmeyer et al, 2018). Brandstädter et al (2012) and Uygur (2019) have examined the efficacy of the digital type of response in relation to students' performance. In both studies, their statistical analysis between pre-and post-tests showed improved students' performance when using the digital concept maps in comparison with the paper-and-pencil ones.…”
Section: Introductionmentioning
confidence: 99%
“…Peta konsep membantu siswa dalam mengorganisasikan informasi, menggambarkan hierarki konsep, dan menunjukkan bagaimana konsep-konsep tersebut saling terkait. Di sisi lain, peta konsep juga membantu siswa dalam hal meregulasi dan menghubungkan informasi baru yang didapatkan setelah kegiatan observasi (Uygur, 2019) dan membantu siswa agar lebih mudah membangun dan memvisualisasikan tingkat pemahamannya (Kinchin, Möllits, & Reiska, 2019;Won, Krabbe, Ley, Treagust, & Fischer, 2017). Jadi, pengembangan peta konsep memerlukan kemampuan siswa dalam mengorganisasikan pemikiran mereka tentang konsep dengan menuliskan atau membuat hubungan antar konsep.…”
unclassified